PENGARUH MOTIVASI KERJA, BUDAYA ORGANISASI, DAN PEMBERIAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. NASMOCO BAHANA MOTOR BANTUL YOGYAKARTA - Munandar, Faris; Bidayati, Utik (Jurnal Fokus Manajemen Bisnis, 2015)
This study aims to determine the effect of Employee Engagement, Organizational Commitment, and Transformational Leadership on Readiness for Change in employees of Ahmad Dahlan University, Yogyakarta. The population in this study were 357 employees of Ahmad Dahlan Yogyakarta University and the sample used was 103 people, the sampling technique used was purposive sampling with sample criteria were permanent employees with a minimum working period of one year and had not moved to campus 4 UAD. The data analysis tool used is multiple linear regression test. The results of this study indicate that Employee Engagement has no effect on Readiness for Change at Ahmad Dahlan University employees. Organizational Commitment affects the Readiness for Change of Ahmad Dahlan University employees. Transformational Leadership has no effect on Readiness for Change at Ahmad Dahlan University employees. And employee engagement, organizational commitment, and transformational leadership simultaneously influence the readiness for change in employees of Ahmad Dahlan University, Yogyakarta.